Stereotyp Europy w dyskursie radykalnego ruchu prawosławnego w Rosji. Część II - Zemszał, Piotr (Przegląd Wschodnioeuropejski, 2023)
The presented text focuses on the stereotype of Europe in the discourse of the radical Orthodox Church in Russia. A difference between a generally accepted concept and a discursively conditioned stereotype, as understood by W. Lippmann, represents an important methodological aspect. The empirical material was selected from over 70 publications from https://3rim.info/, a religious news aggregator. Its analysis allowed the author to reach the following conclusions: in this discourse, a concept of EUROPE undergoes a significant axio-logical reinterpretation and expansion exceeding the concept profiling, and creating a stereotype characteristic of the studied discourse.